Determination of the Causative Agents of Bacteremia in Children under 5 Years and their Susceptibility Pattern to the Antibiotics (Global Journal of Medical Research, 2014)
Objective: To determine the causative agents of bacteremia in children under 5 years and their susceptibility to the commonly used antibiotics. Methods: This was a cross-sectional study on children (aged from 1 day to 5 years) admitted to the paediatric ward. The patients included all newborn babies and children admitted with fever and suspected of having sepsis. All the included children were clinically diagnosed for septicemia following strict aseptic precautions and the blood sample was taken. Blood culture were done by standard method. Results: The overall incidence of bacteremia was 23.1%. The incidence of bacteremia was higher among the chidren of age group 13-60 month (38.1%) than
Keywords: bacteremia; incidence; children; bacterial isolates